Understanding perception of food types in terms of their structures: the missing links. Issue 2 (10th February 2017) - Scholten, Elke
Abstract : Guest editor Elke Scholten introduces the 'Structure & Sensory' themed collection of Food & Function, focusing on aspects related to the structuring of food towards tailored properties and the perception of foods by consumers.